2013
DOI: 10.1016/j.jjcc.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid as an independent predictor of mortality in high-risk patients with obstructive coronary artery disease

Abstract: SUA may be a significant predictor of cardiac and overall mortality, independent of classic risk factors in high-risk patients with obstructive CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 32 publications
1
26
0
3
Order By: Relevance
“…24 Because this study only used one SNP in the SLC2A9 gene as an instrumental variable, we also calculated CORs and CHRs using a single SNP in SLC2A9 (rs12498742), which is in high linkage disequilibrium with the one used by Palmer et al The COR for prevalent CAD was not significant (data not shown) and estimates for fatal events derived from this analysis were very similar compared with the results obtained for GRS 8 (Supplemental Table 6), which is expected because the SLC2A9 SNP shows by far the strongest association with UA. Regarding all-cause mortality and cardiovascular mortality, most studies find that serum UA is an independent predictor of cardiovascular end points, especially in patients with CAD, 17,30,[33][34][35] but some studies reported the opposite. 29,36,37 Possible explanations for diverging results could be sex-specific effects, 38 an interaction with kidney function, 39 or the possibility that UA might turn pro-oxidant under certain conditions (e.g., CAD).…”
Section: Discussionmentioning
confidence: 99%
“…24 Because this study only used one SNP in the SLC2A9 gene as an instrumental variable, we also calculated CORs and CHRs using a single SNP in SLC2A9 (rs12498742), which is in high linkage disequilibrium with the one used by Palmer et al The COR for prevalent CAD was not significant (data not shown) and estimates for fatal events derived from this analysis were very similar compared with the results obtained for GRS 8 (Supplemental Table 6), which is expected because the SLC2A9 SNP shows by far the strongest association with UA. Regarding all-cause mortality and cardiovascular mortality, most studies find that serum UA is an independent predictor of cardiovascular end points, especially in patients with CAD, 17,30,[33][34][35] but some studies reported the opposite. 29,36,37 Possible explanations for diverging results could be sex-specific effects, 38 an interaction with kidney function, 39 or the possibility that UA might turn pro-oxidant under certain conditions (e.g., CAD).…”
Section: Discussionmentioning
confidence: 99%
“…This metabolic pathway is source of production of oxygen-free radicals (3). Several recent studies supported the association between serum uric acid (SUA) and cardiovascular diseases (CVDs) (4-8). Increased SUA concentrations are associated with hypertension, atherogenic dyslipidemia, diabetes, age, alcohol consumption and renal failure.…”
Section: Introductionmentioning
confidence: 96%
“…The SUA level is significantly higher in patients with CAD than in healthy controls [4]. Moreover, multiple prospective studies indicated that elevated SUA level was independently associated with the increased cardiovascular morbidity and mortality in the general population [5] as well as among subjects with significant, angiography defined CAD [6,7] independent of traditional risk factors.…”
Section: Introductionmentioning
confidence: 99%